2016
DOI: 10.4300/jgme-d-15-00487.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Paging Reminders on Fellowship Conference Attendance: A Multi-Program Randomized Crossover Study

Abstract: Paging reminders prior to a regularly scheduled conference had no effect on overall attendance in this study. Fellows reported that clinical obligations were a major barrier to conference attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The results of this study differ from Smith and colleagues, who found that reminder pages had no overall effect on conference attendance for fellows; however, no sample size justification was provided in that study, making it difficult to evaluate the likelihood of a false-negative finding. 7 Our study differs in several ways: the timing of the reminder page (5 minutes vs 30 minutes prior to the conference), the method by which attendance was recorded (by an independent observer vs learner sign-in), and the time that attendance was recorded (2 prespecified times vs continuously). As far as we know, our study is the first to evaluate the nudge effect of reminder text pages on internal medicine resident attendance at conferences, with attendance taken by an observer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study differ from Smith and colleagues, who found that reminder pages had no overall effect on conference attendance for fellows; however, no sample size justification was provided in that study, making it difficult to evaluate the likelihood of a false-negative finding. 7 Our study differs in several ways: the timing of the reminder page (5 minutes vs 30 minutes prior to the conference), the method by which attendance was recorded (by an independent observer vs learner sign-in), and the time that attendance was recorded (2 prespecified times vs continuously). As far as we know, our study is the first to evaluate the nudge effect of reminder text pages on internal medicine resident attendance at conferences, with attendance taken by an observer.…”
Section: Resultsmentioning
confidence: 99%
“…5 Unfortunately, competing priorities, including patient care and trainee supervision, may contribute to an action-intention gap among house staff that reduces attendance. [6][7][8] Low attendance at morning reports represents wasted effort and lost educational opportunities; therefore, strategies to increase attendance are needed. Of several methods studied, more resource-intensive interventions (eg, providing food) were the most successful.…”
mentioning
confidence: 99%